Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper investigates the impact of exchange rate movements on private consumption in Uruguay. Uruguay is a highly dollarized economy, which makes the relationship between exchange rate movements and private consumption particularly complex. The paper shows that a large share of Uruguayan households is liquidity constrained, which allows the transitory real income shocks brought about by exchange rate pass-through to have a significant impact on consumption. Moreover, exchange rate pass-through is highly heterogenous, with relative prices of durables increasing (decreasing) following a depreciation (appreciation). This creates incentives for households to engage in intertemporal substitution where they buy durables when they are relatively cheaper. Data from Input-Output tables show that Uruguay produces a nontrivial amount of the tradable, durable goods it consumes, opening the door to contractionary depreciations. The results offer a potential explanation for the often noted 'excess volatility of consumption' in emerging markets for the case of Uruguay.